Use of Brown Seaweed Extracts as Bio-fertilizers and their Effects on the Carrageenan Yield, Ice-ice Disease Occurrence, and Growth Rate of the Red Seaweed Kappaphycus striatus - TAHILUDDIN, Albaris; IRIN, Sitti Sheha; JUMADIL, Katrina; MUDDIHIL, Radzwina; TERZİ, Ertuğrul (Yuzuncu Yil Universitesi Tarim Bilimleri Dergisi, 2022)
Kappaphycus striatus is one of the most important eucheumatoid species that is widely farmed worldwide. In the southern Philippines, where the initial farm was established, sluggish growth of farmed Kappaphycus species brought about by the poor quality of planting materials and extensive farming resulting in unproductive farms and frequent ice-ice outbreaks have been a hindrance in increasing the seaweed production. As a result, farmers have led to the application of inorganic fertilizers as nutrient enrichment for Kappaphycus. However, inorganic or chemical fertilizers always pose negative impacts on the environment. Hence, in this study, a preliminary investigation on the potential use of extracts of brown seaweeds Sargassum cristaefolium and Turbinaria conoides as bio-fertilizers was tested on K. striatus for their growth rate, carrageenan yield, and ice-ice disease occurrence. Seaweed liquid extracts (SLE): S. cristaefolium (SC), T. conoides (TC), combination of SC and TC (MX), and control (C) were utilized as bio-fertilizers for K. striatus. SLE-enriched K. striatus seedlings were cultivated in a seaweed farm using the fixed-off bottom method for 45 days. Results revealed that the specific growth rates of all SLE treatments were significantly higher than no SLE treatment at day 45. The percentage of ice-ice disease and the yield of carrageenan did not differ among treatments. Enrichment of K. striatus using SLE of two selected brown seaweeds before out-planting could improve growth rates while not affecting the ice-ice disease occurrence and carrageenan yield. Hence, formulated SLE from brown seaweeds S. cristaefolium and T. conoides can be used as potential bio-fertilizers for Kappaphycus cultivation.
Keywords: Bio-fertilizer; Kappaphycus striatus; Sargassum; Seaweed liquid extract; Turbinaria; Balıkçılık Yönetimi; Fisheries Management; 2. Zero hunger; 15. Life on land; 6. Clean water